Expression of the Inhibitory Receptor TIGIT Is Up-Regulated Specifically on NK Cells With CD226 Activating Receptor From HIV-Infected Individuals - Yin, Xiaowan; Liu, Tingting; Wang, Zhuo; Ma, Meichen; Lei, Jie; Zhang, Zining; Fu, Shuai; Fu, Yajing; Hu, Qinghai; Ding, Haibo; Han, Xiaoxu; Xu, Junjie; et al. (Frontiers in Immunology, 2018)
Natural killer (NK) cells are important for maintenance of innate immune system stability and serve as a first line of defense against tumors and virus infections; they can act either directly or indirectly and are regulated via co-operation between inhibitory and stimulatory surface receptors. The recently reported inhibitory receptor, TIGIT, can be expressed on the NK cell surface; however, the expression level and function of TIGIT on NK cells during HIV infection is unknown. In this study, for the first time, we investigated the expression and function of TIGIT in NK cells from HIV-infected individuals. Our data demonstrate that the level of TIGIT is higher on NK cells from patients infected with human immunodeficiency virus (HIV) compared with HIV-negative healthy controls. TIGIT expression is inversely correlated with CD4+ T cell counts and positively correlated with plasma viral loads. Additionally, levels of the TIGIT ligand, CD155, were higher on CD4+ T cells from HIV-infected individuals compared with those from healthy controls; however, there was no difference in the level of the activating receptor, CD226, which recognizes the same ligands as TIGIT. Furthermore, TIGIT was found to specifically up-regulated on CD226+ NK cells in HIV-infected individuals, and either rIL-10, or rIL-12 + rIL-15, could induce TIGIT expression on these cells. In addition, high TIGIT expression inhibited the production of interferon-gamma (IFN-γ) by NK cells, while TIGIT inhibition restored IFN-γ production. Overall, these results highlight the important role of TIGIT in NK cell function and suggest a potential new avenue for the development of therapeutic strategies toward a functional cure for HIV.